The impacts of inflation on developing countries / Nurul Adira Baharuddin - Baharuddin, Nurul Adira (Universiti Teknologi Mara Perlis, 2020)
This study is undertaken to identify the impacts of inflation on developing country. The data for this study is 10 years and it was collected from World Bank Data. This study is using inflation as the dependent variable as proxy consumer price index (CPI). Independent variable used in this study are gross domestic product (GDP), unemployment rate, money supply, investment, and imported goods and services. This study used Static Panel Data to get regression results. It is found that gross domestic product (GDP), money supply and imported goods and services are significant relationship in give impacts in inflations. Meanwhile, unemployment rate and investment are not significant relationship to the impacts of inflation.